Invisible Mining: Addressing EU Raw Material Challenges Through Technological Innovation - Vitor Correia; Eberhard Falck; Marko Komac (Intereconomics, 2024)
This paper examines the challenges in implementing the EU's raw materials policy, including conflicts between minerals extraction, Green Deal objectives, nature restoration targets and public opposition to mining projects. It explores innovative approaches such as invisible mining, enabled by advancements in robotics and miniaturisation, comprehensive and integrated resource recovery principles and materials-as-a-service business models, which can minimise environmental impacts and enhance social acceptability. The paper argues that successful implementation of the EU's Critical Raw Materials Act requires a multifaceted approach, building on technological advances and encompassing policy harmonisation, socio-economic innovation and skills development. By adopting this comprehensive strategy, the EU can create a more sustainable and socially responsible mining industry, addressing the immediate need for critical raw materials while positioning itself as a global leader in responsible mining.
Keywords: O33; Q30; Q56; 330; Raw materials; Raw materials policy; Technical progress; Innovation; EU countries; Rohstoff; Rohstoffpolitik; Technischer Fortschritt; Innovation; EU-Staaten